2017
DOI: 10.5194/acp-17-2881-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Siberian observations on the optimization of surface CO<sub>2</sub> flux

Abstract: Abstract. To investigate the effect of additional CO 2 observations in the Siberia region on the Asian and global surface CO 2 flux analyses, two experiments using different observation data sets were performed for 2000-2009. One experiment was conducted using a data set that includes additional observations of Siberian tower measurements (JapanRussia Siberian Tall Tower Inland Observation Network: JR-STATION), and the other experiment was conducted using a data set without the above additional observations. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…The low latitude (tropical Asia) region released CO 2 to the atmosphere during summer, whereas a reverse pattern was observed in winter, which is evidently observed in the simulated results as shown in Figure 12. Our result is consistent with previous findings indicating that northern temperate and high latitude ecosystems are strong carbon sinks [4,43,44] and tropical land regions are strong carbon sources [9].…”
Section: Spatio-temporal Distribution Of Nee Fluxsupporting
confidence: 93%
“…The low latitude (tropical Asia) region released CO 2 to the atmosphere during summer, whereas a reverse pattern was observed in winter, which is evidently observed in the simulated results as shown in Figure 12. Our result is consistent with previous findings indicating that northern temperate and high latitude ecosystems are strong carbon sinks [4,43,44] and tropical land regions are strong carbon sources [9].…”
Section: Spatio-temporal Distribution Of Nee Fluxsupporting
confidence: 93%
“…These studies indicate that for CT2016, the carbon sink in Europe may be underestimated, while in boreal Eurasian, it may be significantly overestimated. Since there are only very few XCO2 observations from both GOSAT and OCO-2 in this area, our estimates are very close to the prior and much weaker than those found by Saeki et al (2013) and Kim et al (2017), indicating that the land sink in the Eurasian Boreal is underestimated in this study. Combined the land sinks of Europe and Eurasian Boreal, the inverted land sinks of GOSAT (-0.86 Pg C yr -1 ) is comparable with CT2016 (-0.92 Pg C yr -1 ), indicating that the land sink in Europe inferred from GOSAT may be also overestimated to a certain extent.…”
Section: Global Carbon Budgetsupporting
confidence: 74%
“…One explanation for the large sink in CT2016 in this area is that there is a mutual compensation for carbon sinks between Europe and Eurasian Boreal because of the large differences in the amount of observations between these two areas. Kim et al (2017) found that with the addition of Siberian in-situ measurements to their inversion system, the carbon uptake in Europe was enhanced while it decreased in the boreal Eurasian. Saeki et al (2013) also reported that more CO2 observations over Siberian used in the inversion system would weaken the summer carbon uptake in this area.…”
Section: Global Carbon Budgetmentioning
confidence: 99%
“…Refer to Tsuruta et al (2017 Analysis of the trends and the diurnal, weekly and seasonal cycles of CO2 and CH4 mixing ratios derived from the long-term data of the "Japan-Russia Siberian Tall Tower Inland Observation Network" showed that the frequency of identified events of elevated concentration differs for CO2 and CH4 and may reach up to 20% of days in some months (Belikov et al, 2019). These observations made it possible to reduce uncertainties in the biosphere surface CO2 uptake (Kim et al, 2017). Although the CO2 uptake in boreal Eurasia estimated by Kim et al (2017) was about 30% lower than that obtained without the assimilation of Siberian observation data, Siberia still remains a key contributor to the terrestrial CO2 sink in the Northern Hemisphere.…”
Section: Boreal Forests Carbon Balancementioning
confidence: 99%